KIF2C is essential for meiosis and manchette dynamics in male mice - Harima, Ryua; Kishinami, Mayu; Hara, Kenshiro; Tanemura, Kentaro (Frontiers in Cell and Developmental Biology, 2025)
In gametogenesis, microtubules undergo dramatic changes known as microtubule dynamics, and which is important for fertility both male and female. In spermatogenesis, spindle microtubule dynamics occur during meiosis and manchette microtubule dynamics occur in elongated spermatids. In oogenesis, spindle microtubule dynamics occur during meiosis. The microtubule depolymerization protein kinesin-13 family (KIF2A, KIF2B, and KIF2C) plays an important role in microtubule dynamics, and KIF2C is a well-known microtubule depolymerization factor in mitosis. Although the function of KIF2C in mitosis has been extensively studied, its role in meiosis remains unclear. Additionally, the role of microtubule dynamics in manchette formation remains unclear. We generated germ cell-specific Kif2c conditional knockout (Kif2c cKO) mice to elucidate KIF2C function in germ cells. Kif2c cKO male mice showed chromosomal misalignment at meiotic metaphase, abnormal manchette morphology and delayed manchette disassembly, which led to a significant increase in apoptosis. Furthermore, Kif2c cKO male mice were completely infertile. Therefore, KIF2C plays an important role in chromosomal alignment in male meiosis and in manchette dynamics in elongated spermatids. In contrast, Kif2c cKO female mice were sufficiently fertile, and only minor defects were observed in chromosome alignment in meiosis. This study demonstrates, for the first time, that KIF2C is important for microtubule dynamics of spermatogenesis to achieve male fertility, but not for female fertility.